Construction of Hospital by Laws in Realizing Hospital Clinical Governance - Iklima Anggarani Purbaningrum; Gayatri Dyah Suprobowati (International Journal of Law, Crime and Justice, 2024)
Every hospital is required to have an obligation to prepare and implement its internal hospital regulations or hospital by laws. The implementation of hospital by laws is regulated in detail in the Decree of the Minister of Health long before the enactment of Law Number 44 of 2009 concerning Hospitals. This study analyzes in more depth the construction of regulations on hospital by laws in Indonesia and the implementation of hospital by laws as internal regulations in Hospitals.